Neutrophil-derived Oxidants and Proteinases as Immunomodulatory Mediators in Inflammation - V. Witko-Sarsat; B. Descamps-Latscha (Mediators of Inflammation)
Neutrophils generate potent microbicidal molecules via the oxygen-dependent pathway, leading to the generation of reactive oxygen intermediates (ROI), and via the non-oxygen dependent pathway, consisting in the release of serine proteinases and metalloproteinases stored in granules. Over the past years, the concept has emerged that both ROI and proteinases can be viewed as mediators able to modulate neutrophil responses as well as the whole inflammatory process. This is well illustrated by the oxidative regulation of proteinase activity showing that oxidants and proteinases acts is concert to optimize the microbicidal activity and to damage host tissues. ROI and proteinases can modify the activity of several proteins involved in the control of inflammatory process. Among them, tumour necrosis factor-α and interleukin-8, are elective targets for such a modulation. Moreover, ROI and proteinases are also able to modulate the adhesion process of neutrophils to endothelial cells, which is a critical step in the inflammatory process.